Penerapan Kebijakan Kamar Rawat Inap Standar Di Rumah Sakit Di Kota Parepare - Budiawan, Rainer Schumacher Rafael; Yusuf, Syarifuddin; Majid, Makharajani; Usman, Usman; Muin, Herlina (Jurnal Ilmiah Manusia Dan Kesehatan, 2026)
Equitable and high-quality healthcare is a fundamental right that must be fulfilled for all citizens. In an effort to reform the inpatient care system, which has long been considered unjust, the Indonesian government through BPJS Kesehatan has established the Standard Inpatient Class (KRIS) policy. This policy aims to equalize the standards of inpatient rooms in all hospitals regardless of the participant's economic status. This study aims to evaluate the readiness of hospitals in Parepare City in implementing the KRIS policy. The research uses a qualitative approach with observation techniques and in-depth interviews involving 12 informants from three hospitals: RS. Andi Makkasau, RS. dr. Hasri Ainun Habibie, and RS. Fatima. The aspects analyzed include facilities and infrastructure, management, human resources, and funding. The findings show that all hospitals have allocated 40–45% of beds to support KRIS and formed dedicated implementation teams. However, fulfillment of the 12 KRIS criteria still faces several challenges, especially regarding oxygen outlets and the nurse call system. The study concludes that despite technical and resource challenges, hospitals in Parepare City are generally ready to implement KRIS ahead of the national deadline in June 2025. Hospitals are advised to conduct in-depth analysis on unmet criteria, strengthen KRIS teams through training, broaden policy socialization, and optimize budgeting and time management strategies.